“Pengaruh Faktor Sosial, Lingkungan, dan Kebijakan Keamanan terhadap Tingkat Kriminalitas di Kawasan Perkotaan” - Peter Guntara; Gusni Cahaya Putri; Evandito Raihan Prayoga (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study provides a comprehensive understanding of how social, economic, and physical environmental factors interact in influencing crime rates in urban areas, as well as how security policies and urban facilities contribute to their prevention. Using a normative juridical approach, the research finds that social factors such as community disorganization, weak family control, economic pressure, and peer group influence constitute primary determinants that drive the emergence of deviant behavior. These factors are further exacerbated by poor physical environmental conditions, including inadequate lighting, insufficient public infrastructure, and spatial arrangements that do not support natural surveillance, as explained in CPTED theory. From a policy perspective, Indonesia’s positive legal framework provides the normative foundation for the administration of public security through the Criminal Code (KUHP), the Law on the Indonesian National Police, and various regulations governing public order and safety. However, the effectiveness of these legal provisions largely depends on the adequacy of urban security facilities and the state’s capacity to translate legal norms into technical policies that are responsive to the dynamics of urban society. The provision of street lighting, CCTV, orderly spatial planning, and sufficient law enforcement capacity not only plays a preventive role but also forms an essential component of the criminal evidence system. Thus, this study emphasizes that efforts to reduce urban crime require an integrative approach that combines social, economic, physical environmental, and legal dimensions in a sustainable manner. The formulation of urban security policies should be preventive, evidence-based, and aligned with criminological theories and applicable legal norms. Such an approach is expected to foster urban spaces that are safer, more inclusive, and more equitable for all residents.